Curcumin induces apoptotic cell death via Oct4 inhibition and GSK-3 activation in NCCIT cells - Yun, Ji Ho; Park, Young Gyun; Lee, Kyung-Mi; Kim, Jungho; Nho, Chu Won (WILEY, 2015)
ScopeOctamer-binding transcription factor 4 (Oct4) is a key regulator of pluripotent embryonic stem cell maintenance. However, increasing evidence has suggested that Oct4 is also expressed in cancer stem cells (CSCs) and is associated with tumor progression and chemoresistance. Curcumin (CUR) is a widely used cancer chemopreventive agent, and it has been used to treat several diseases including cancers. Here, we investigated whether CUR-induced apoptotic cell death by inhibiting Oct4 levels and examining molecular mechanisms in NCCIT human embryonic carcinoma cells. Methods and resultsCUR significantly inhibited Oct4 transcription levels in a dose-dependent manner by dual luciferase experiment, also decreased mRNA and protein levels in NCCIT human embryonic carcinoma cells, which express high levels of endogenous Oct4. Interestingly, we found that CUR treatment increased apoptotic cell death including subG0/G1 contents, cleavage caspases, and pro-apoptotic protein, as confirmed with a series of loss-of-function experiments using Oct4 siRNA. Furthermore, CUR induced marked total level of glycogen synthase kinase 3 beta (GSK-3), resulting in an increase in apoptotic cell death, was evaluated using chemical inhibitor of GSK3-3. ConclusionThese data suggest that CUR induces apoptotic cell death through Oct4 inhibition and GSK-3 activation. Thus, CUR may be a useful cancer chemopreventive agent to suppress tumor progression or to improve chemoresistance by eliminating CSCs.
Keywords: CANCER STEM-CELLS; TRANSCRIPTION FACTOR; COLORECTAL-CANCER; BETA-CATENIN; MESENCHYMAL TRANSITION; DOWN-REGULATION; SELF-RENEWAL; EXPRESSION; PATHWAY; CHEMOPREVENTION